Health Care of adolescents complying with socio-educational measure (Research, Society and Development, 2022)
Adolescence is an important moment for the adoption of good practices and establishment of autonomy, but also of exposure to behavioral risk factors, with short- and long-term health implications. However, health care in the context of deprivation of liberty occupies a secondary level, as with health promotion actions, both of which are essential to integrate adolescents into the social context and to promote protective factors and reduce risks. Thus, this research aimed to analyze the perception of adolescents and professionals inserted in a socio-educational care unit about health care in adolescence. This is a methodological study of qualitative nature, conducted at the Centro Socioeducational São Miguel, the adolescents aged 15 to 18 years and professionals from the center participated in the research. The analysis showed a lack of knowledge about health care. Considering, therefore, that socio-educational care units and socio-educational measures, originally conceived as strategies of social reintegration, point more to weaknesses than to the success of their purposes, it is believed that the restorative character of the application of socio-educational measures needs to be associated with care and promotion of health and quality of life, from the creation of educational strategies that allow a possible change of behavior, generated through motivation when acquiring knowledge about a given theme, associated with the desire for healthy life practices that generate quality of life.